Egalitarian binds dynein light chain to establish oocyte polarity and maintain oocyte fate. - Navarro, C.; Puthalakath, H.; Adams, J.M.; Strasser, A.; Lehmann, R. (Nature Cell Biology, 2004)
In many cell types polarized transport directs the movement of mRNAs and proteins from their site of synthesis to their site of action, thus conferring cell polarity. The cytoplasmic dynein microtubule motor complex is involved in this process. In Drosophila melanogaster, the Egalitarian (Egl) and Bicaudal-D (BicD) proteins are also essential for the transport of macromolecules to the oocyte and to the apical surface of the blastoderm embryo. Hence, Egl and BicD, which have been shown to associate, may be part of a conserved core localization machinery in Drosophila, although a direct association between these molecules and the dynein motor complex has not been shown. Here we report that Egl interacts directly with Drosophila dynein light chain (Dlc), a microtubule motor component, through an Egl domain distinct from that which binds BicD. We propose that the Egl-BicD complex is loaded through Dlc onto the dynein motor complex thereby facilitating transport of cargo. Consistent with this model, point mutations that specifically disrupt Egl-Dlc association also disrupt microtubule-dependant trafficking both to and within the oocyte, resulting in a loss of oocyte fate maintenance and polarity. Our data provide a direct link between a molecule necessary for oocyte specification and the microtubule motor complex, and supports the hypothesis that microtubule-mediated transport is important for preserving oocyte fate.